A ZAKAT HASIL PERKEBUNAN DALAM TINJAUAN HUKUM ISLAM Di Pekon Kenali Kecamatan Belalau Kabupaten Lampung Barat: zakat - Putri, Gusti Adinda; khoiruddin; Susi Nurkholidah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose – This study aims to analyse the compliance of muzakki ((people who give zakat) in paying zakat on agricultural produce, particularly coffee and pepper, in Pekon Kenali, Belalau Subdistrict, West Lampung Regency. The focus of the study is on the method of calculating zakat, the community's understanding of the provisions of nisab and zakat rates, and the mechanism of distribution and management based on the perspective of zakat fiqh. Method – To answer the questions posed in this study, a qualitative approach was used with descriptive analytical empirical research and in-depth data collection techniques, including direct observation in the field, interviews with 5 (five) informants who are plantation owners, and documentation. Result –The results of the study indicate that zakat from agricultural produce has significant economic potential, considering that more than 95% of households in Pekon Kenali are engaged in farming, with harvest income reaching up to Rp.299 million per season or year. However, this potential has not been optimised due to low public understanding of the nisab requirements, zakat rates (5%–10%), and payment timelines that do not align with Islamic law. The amount of zakat paid is generally below 2%, and its distribution is conducted individually without going through official institutions. Implication – As a practical implication, can be used as a reference for the community to understand how to properly implement zakat in accordance with Islamic law, as well as for the government, particularly the local village head and zakat institutions, in promoting marketing strategies that are in line with the community's behaviour in paying zakat. Therefore, continuous education and the establishment of a structured zakat management system in accordance with Islamic law are necessary.